Residential greenness for mitigating impacts of extreme heat events on depression and supporting mental health - Yang, Ying; Zhang, Yixin; Sheng, Shaojie (Frontiers in Public Health, 2023)
1. Plants provide photosynthesis for urban ecosystems; their transpiration cooling effect can regulate the local environment temperature through an evaporative process and filter air pollutants through phytoremediation, purifying the environment.2. Extreme heat episodes pose a salient risk to the well-being resulting in factors in depression.3. RGS can alleviate the impact of heat waves on mental health through climate improvement, overcoming emotional barriers, and interacting with green Spaces.4. RGS provides ecosystem services for reducing extreme heatwaves' impact on depression.periods of extreme heat events is put forth.